Early identification of promiscuous attributes of aldose reductase inhibitors using a DMSO-perturbation assay. Issue 2 (15th January 2020) - Tomohara, Keisuke; Hasegawa, Naoto; Adachi, Isao; Horino, Yoshikazu; Nose, Takeru
Graphical abstract: Abstract: Aldose reductase (AR) inhibitors are used clinically to treat long-term diabetic complications. Previous studies reported a series of AR inhibitory candidates, but unfortunately the mode of inhibition was poorly described due mainly to the lack of readily available methods for evaluating the specificity. The present study examined the AR inhibitory effects of novel synthetic hydantoins and their structural relatives, some of which were obtained from chemically engineered extracts of natural plants, and discovered several novel AR inhibitors with moderate inhibitory activity. The identified inhibitors were then subjected to a two-step mechanistic characterization using a detergent-addition assay and our novel dimethyl sulfoxide (DMSO)-perturbation assay. The detergent-addition assay revealed aggregation-based inhibitors, and the subsequent DMSO-perturbation assay identified nonspecific binding inhibitors. Thus, the present study demonstrates the usefulness of the DMSO-perturbation screen for identifying nonspecific binding characteristics of AR inhibitors.